GSSA: uma arquitetura de segurança para grid services - Oliveira, Claudio Rodolfo Sousa de (2009)
Existing mechanisms for Grid Service (GS) security control do not allow transparently binding different user roles and permissions in the access control for operations and resources. After successfuly authenticated a user may access all registered services. This dissertation presents the GS Security Architecture (GSSA), a security architecture for GSs based on the Open GSs Architecture (OGSA), which aims to fullfil this gap. GSSA also provides funcionalites for authentication, log keeping for non-repudiation, auditing and accountability, secure data exchange between GS, and the execution of GSs from withn Web Services (WS). This dissertation also describes an implementation of the GSSA, named GS Security Proxy (GSSP), and evaluates the use of this proxy in a telemedicine application.